Being #wanitasalihah: Representations of salihah women on TikTok - Fernando, Henky; Galuh Larasati, Yuniar; Cahyani, Novita (Yayasan Irwan Abdullah Cendekia, 2023)
Being a salihah woman represented by TikTok, social media users have formed complex symbols and meanings. This study describes the representation of salihah women and reflects the meaning of salihah women in TikTok social media. This study uses the netnography method with a qualitative descriptive approach. Data collection in this study begins with a reading process on 1.6 thousand video posts disseminated on TikTok social media using the hashtag #wanitasalihah. Data analysis is carried out through immersive methods by describing, classifying, and interpreting data thematically to reveal the meaning represented in describing the concept of pious women. The findings in this study show that the representation of pious women is represented in ideological and symbolic themes.